Management of giant cell tumor of bone in the era of denosumab: A case series and review of the literature - Anjan Bera; Shatarupa Dutta; Aparajita Sadhya; Soham Gangopadhyay; Debosmita Bhattacharyya; Srikrishna Mandal; Manna, Debojyoti (Asian Journal of Medical Sciences, 2023)
Giant cell tumor (GCT) of the bone also known as osteoclastoma typically arises from the meta-epiphyseal region of the long bone and comprises 5% of all bone tumors and 20% of benign bone tumors. Understanding pathogenesis is the key to successful systemic therapy with denosumab, a RANK-ligand inhibitor. In this context, we report seven GCT bone-treated denosumab and radiotherapy cases with a diverse clinical presentation from our institute, NRS Medical College, and Hospital Kolkata.